Ethernet in the first mile : the IEEE 802.3ah EFM standard - Beck, Michael, 1976- (McGraw-Hill's AccessEngineering., 2005)
"Ethernet in the First Mile annotates and explains the complex language of the standard document. With a strong focus on how EFM dovetails with other standards in real world applications, this detailed reference is essential for readers developing new products and services, as well as for networking consultants and advanced users."--Jacket.